Life is elsewhere - Kundera, Milan (b, 2000)
The author intially intended to call this noel, The Lyrical Age. The lyrical age, according to Kundera, is youth, and this novel, above all, is an epic of adolescence an ironic epic that tenderly erodes scarosanct values: childhood, motherhood, revolution, and even poetry. Jaromil is in fact a poet. His mother made him a poet and accompanies him (figuratively) to his love bed and (literally) to his deathbed. A ridiculous and touching character, horrifying and totally innocent ("innocence with its bloody smile"!), Jaromil is at the same time a true poet. He's no creep, he's Rimbaud. Rimbaud entrapped by the communist revolution, entrapped in a somber farce.
Keywords: Mothers and sons -- Fiction; Poets -- Fiction; Communism -- Fiction